On Volatility Swaps for Stock Market Forecast: Application Example CAC 40 French Index - Halim Zeghdoudi; Abdellah Lallouche; Mohamed Riad Remita (Journal of Probability and Statistics)
This paper focuses on the pricing of variance and volatility swaps under Heston model (1993). To this end, we apply this model to the empirical financial data: CAC 40 French Index. More precisely, we make an application example for stock market forecast: CAC 40 French Index to price swap on the volatility using GARCH(1,1) model.